Acute and long-term psychiatric side effects of mefloquine: A follow-up on Danish adverse event reports. Issue 1 (January 2015) - Ringqvist, Åsa; Bech, Per; Glenthøj, Birte; Petersen, Eskild
Summary: Background: The aim of the study was to explore the profile of acute and long-term psychiatric side effects associated with mefloquine. Methods: Subjects ( n = 73) reported to a Danish national register during five consecutive years for mefloquine associated side effects were included. Acute psychiatric side effects were retrospectively assessed using the SCL-90-R and questions based on Present State Examination (PSE). Subjects reporting suspected psychotic states were contacted for a personal PSE interview. Electronic records of psychiatric hospitalizations and diagnoses were cross-checked. Long-term effects were evaluated with SF-36. SCL-90-R and SF-36 data were compared to age- and gender matched controls. Results: In the SCL-90-R, clinically significant scores for anxiety, phobic anxiety and depression were found in 55%, 51%, and 44% of the mefloquine group. Substantial acute phase psychotic symptoms were found in 15% and were time-limited. Illusions/hallucinations were more frequently observed among women. Cases of hypomania/mania in the acute phase were 5.5%. Significant long-term mental health effects were demonstrated for the SF-36 subscales mental health (MH), role emotional (RE), and vitality (VT) in the mefloquine group compared to matched controls. Conclusion: The most frequent acute psychiatric problems were anxiety, depression, and psychotic symptoms. Data indicated that subjects experiencing acute mefloquine adverse side effects may develop long-term mental health problems with a decreased sense of global quality of life with lack of energy, nervousness, and depression.